Pelatihan Pemanfaatan Artificial Inteligence dalam Membuat Media Pembelajaran - N, Renny Afriany; Sinaga, Rudolf; Samsinar, Samsinar; Frangky, Frangky (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2025)
Education in Indonesia faces challenges in adopting modern technology, particularly in developing effective and engaging learning media. Teachers in the Cross-School Learning Community of Cluster II Anggrek in Jambi City still use conventional methods that are less adaptive to student needs. The utilization of AI technology such as Gamma AI can help create more efficient, innovative, and interactive learning media. The training was carried out systematically with four main modules: Introduction to Gamma AI, Creating Presentations, Tips and Tricks, and Evaluation and Application. The methods used included demonstrations, hands-on practice, interactive discussions, and evaluation of training outcomes. The activity involved 30 teacher participants from the community and was conducted on July 16, 2024, at the SD Negeri 96 Kota Jambi hall. This training successfully improved teachers' competencies in utilizing Gamma AI to create more engaging and interactive learning media. Teachers were able to save time in creating materials, use data for personalized learning, and enhance student engagement through AI-based content. The main output of the activity was the improvement of learning quality in schools within the community and the strengthening of teachers' digital competencies.